1992
DOI: 10.1002/pola.1992.080300615
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and phase‐transfer catalytic activity of crown ethers bound to microporous polystyrene resins by oxyethylene spacers

Abstract: Crown ethers bound to microporous polystyrene resins by oxyethylene spacers were prepared by the reaction of monoazacrown ethers with 2‐tosyloxyethoxymethylated or 2‐(2‐tosyloxyethoxy)ethoxymethylated polystyrene resins crosslinked with 2 mol % of divinylbenzene. The activity of the immobilized lariat crowns for halogen exchange reactions under triphase conditions has been studied as a function of catalyst structure, loading, substrate structure, reagent structure, and solvent. The lariat catalysts with extra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Lariat ethers have been designed as cation complexing agents which exhibit complexation behavior similar to crown ethers, but with a three-dimensional binding character. 10,11 Also, as efficient organic ligands, lariat crown ethers meet the requirement of rapid, strong, and three-dimensional cation binding, and can mimic the properties of natural ionophores. 12 In connection with these findings, and in a continuation of our interest in synthesizing macrocyclic crown compounds containing heterocyclic moieties, 13 we report here the synthesis of a series of 18-21-membered azacrown macrocycles fused with two 1,2,4-triazole rings, containing N and O inside the macrocyclic ring as donor atoms and possessing pendent thiol groups as precursors for the synthesis of lariat thioether macrocycles.…”
mentioning
confidence: 99%
“…Lariat ethers have been designed as cation complexing agents which exhibit complexation behavior similar to crown ethers, but with a three-dimensional binding character. 10,11 Also, as efficient organic ligands, lariat crown ethers meet the requirement of rapid, strong, and three-dimensional cation binding, and can mimic the properties of natural ionophores. 12 In connection with these findings, and in a continuation of our interest in synthesizing macrocyclic crown compounds containing heterocyclic moieties, 13 we report here the synthesis of a series of 18-21-membered azacrown macrocycles fused with two 1,2,4-triazole rings, containing N and O inside the macrocyclic ring as donor atoms and possessing pendent thiol groups as precursors for the synthesis of lariat thioether macrocycles.…”
mentioning
confidence: 99%
“…When the spacer chain also contains complexable ether oxygen atoms, using 15-crown-5 as the PTC functional group, catalyst activity is even greater, as observed in halide exchange of KI with I-bromooctane [83].…”
Section: G Effect Of a Spacer Chainmentioning
confidence: 99%
“…4,5 It has been suggested that polystyrene containing crown ethers and mono azacrown ethers were used as phase-transfer catalysts for dehydrohalogenation, addition and substitution reaction and other organic reaction. 6 The major advantages of the polymer-supported phase transfer catalyst [7][8][9][10] are: (1) ease of separation from reaction mixture by filtration; and (2) recycling of the catalyst. This paper describes the synthesis of such polymeric crown ether by direct in this new method.…”
mentioning
confidence: 99%